Global Political Ecology - Saurí i Pujol, David (Documents d'Anàlisi Geogràfica, 2012)
PEET, R.; ROBBINS, P. i WATTS, M.J. (eds.) (2011) Global Political Ecology. London i New York: Routledge, XIV+ 444 p. ISBN 978-0-415-54815-1